On the stability of aluminum oxide in carbon steel melts - E. I. Marukovich; V. Y. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2023)
It is shown that hydrogen atoms in carbon steel melts are surface‑active elements for aluminum oxide microcrystals. Adsorbed hydrogen atoms reduce the interfacial surface energy and increase the resistance of small aluminum oxide microcrystals to coagulation. To reduce their stability in liquid carbon steels, it is necessary to reduce the concentration of dissolved hydrogen in them. Active modifiers reduce the concentration of adsorbed hydrogen. This enhances the process of coagulation of small microcrystals of aluminum oxide into larger particles that can quickly float in the melt.